Glutamatergic Enteric Neurons - Liu, Min-Tsai (J Neurosci, 1997)
We tested the hypothesis that glutamate, the major excitatory neurotransmitter of the CNS, is also an excitatory neurotransmitter in the enteric nervous system (ENS). Glutamate immunoreactivity was found in cholinergic enteric neurons, many of which were identified as sensory by their co-storage of substance P and/or calbindin. Glutamate immunoreactivity was concentrated in terminal varicosities with a majority of small clear synaptic vesicles. The immunoreactivities of both AMPA and NMDA receptor subunits were also detected on neurons in both submucosal and myenteric plexuses. The immunoreactivity of the EAAC1 neuronal glutamate transporter was widespread in both plexuses. Glutamate evoked depolarizing responses in myenteric neurons that had fast and slow components. The fast component was mimicked by AMPA, and the slow component was mimicked by NMDA. The fast component and the response to AMPA mimicked fast EPSPs evoked in 2/AH neurons; moreover, fast EPSPs as well as fast glutamate and AMPA responses were blocked by selective AMPA antagonists and potentiated by the glutamate uptake inhibitor l-(−)-threo-3-hydroxyaspartic acid. These observations demonstrate, for the first time, the presence of glutamatergic neurons and glutamate-mediated neurotransmission in the ENS.